PENGUATAN LITERASI MEMBACA DAN MENULIS MELALAUI PEMBELAJARAN PROJECT-BASED LEARNING PJBL - Hasmawati Hasmawati; Mir'Ah Azizah; Hikmatul Lailaa; Mantasiah Mantasiah (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to describe the forms of project assignments in learning and to elaborate the results of project assignments as well as the improvement of students' reading and writing literacy skills through Project-based learning (PjBL), particularly in Psycholinguistics learning. The population of this study is students of the Department of Foreign Language Education, Faculty of Language and Literature, and the research sample is the 2023 cohort B class students of the Arabic Language Education program selected randomly. This type of research is quasi-experiment, and the data analysis technique used is descriptive statistics. The research results show that PjBL-based is proven to be able to improve students' reading and writing literacy. Quantitatively, descriptively, the improvement is indicated by the students' ability to sift, understand, and relate various theoretical literature sources (reading literacy) into cohesive and argumentative project reports (writing literacy). These results are reinforced by the achievement of very satisfactory final scores, where 77.27% (17 out of 22) of students managed to obtain scores in the range of 81-100 (categories Very Satisfactory and Excellent). This predominantly high score achievement serves as a strong indicator that the learning objectives of Psycholinguistics, which require mastery of academic literacy, have been fully achieved. Therefore, it can be concluded that PjBL is a relevant and successful learning model in integrating course content with the development of literacy competencies for students of the Foreign Language Education Department.